Proceedings of the Tenth International Conference on Information and Knowledge Management 2001
DOI: 10.1145/502585.502618
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to collection selection and results merging for distributed information retrieval

Abstract: We have investigated two major issues in Distributed Information Retrieval (DIR), namely: collection selection and search results merging. While most published works on these two issues are based on pre-stored metadata, the approaches described in this paper involve extracting the required information at the time the query is processed. In order to predict the relevance of collections to a given query, we analyse a limited number of full documents (e.g., the top five documents) retrieved from each collection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…The output and analysis showed that the technique developed the search effectively of the database and fixed search quality was also developed. In [7], the idea of exploiting the scores of each search engine was proposed, where the main information was the relative rank of each result. In [7], different ranking methods were analyzed, for example Borda-fuse which was based on democratic voting, the Borda count, or the weighted borda-fuse, in which search engines were not treated equally [11].…”
Section: Fig 1: Catalogs Per Countrymentioning
confidence: 99%
“…The output and analysis showed that the technique developed the search effectively of the database and fixed search quality was also developed. In [7], the idea of exploiting the scores of each search engine was proposed, where the main information was the relative rank of each result. In [7], different ranking methods were analyzed, for example Borda-fuse which was based on democratic voting, the Borda count, or the weighted borda-fuse, in which search engines were not treated equally [11].…”
Section: Fig 1: Catalogs Per Countrymentioning
confidence: 99%
“…Aggregated search can be compared to federated search [12], metasearch [7] and distributed information retrieval [5], which are all concerned with the retrieval of documents from several sources (e.g. digital libraries, search engines, specialist collections, etc.).…”
Section: Related Workmentioning
confidence: 99%
“…Parallel query processing is required in the search system due to the distributed index and processors. Rasolofo et al [15] propose a collection selection and result merging strategy for distributed Web search system. Orlando et al [16] have developed a distributed Web search engine, MOSE, which utilizes two types of parallelism, task parallelism and data parallelism, in processing queries.…”
Section: Related Workmentioning
confidence: 99%